A Base Nacional Comum Curricular (BNCC) da educação infantil: compreensões e avaliações das professoras da rede municipal de São Borja –RS - Pinheiro, Tania Maria (2022)
This Reflective Report intends to analyze the understandings and evaluations of Preschool teachers, working in the municipal network of São Borja - RS in relation to the National Common Curricular Base - BNCC: Infantile Education, approved in 2017. The BNCC is guiding the curricula and the pedagogical proposals of education systems and networks across the country, from Early Childhood Education to High School. The specific objectives of this work are: to know the Experience Fields of BNCC-Educação Infantil, from the sharing of pedagogical experiences; understand the learning objectives related to the BNCC Fields of Experiences; to elaborate, in the formation circles, collectively with the teachers, pedagogical possibilities of the BNCC-Educação Infantil for the curricula of the infantile schools of the municipal net of São Borja-RS. In a moment of diagnosis, the answers to a questionnaire elaborated and carried through with teachers of the first stage of Basic Education of the municipal schools of são-borjenses were analyzed, observing their opinions on the fulfillment of what is proposed in the BNCC. As a methodology, the research will have a qualitative approach, in order to highlight the specificities and singularities of individuals and the field of study, in addition to reinforcing and qualifying the action of data collection and analysis. Research is also characterized as an intervention. Through the answers to the questionnaires answered by the teachers and verified by the discursive textual analysis (ATD) of Moraes and Galiazzi (2007), it was investigated what are the understandings and the evaluations of the teachers of Early Childhood Education in the municipal network of São Borja/RS about the BNCC and created conversation circles on the topic. Therefore, it can be concluded that the proposal of this research had results of great importance, aimed at understanding the lives of children based on the different fields of experiences that can be experienced by them.